KEPEMIMPINAN, LINGKUNGAN ORGANISASI, MOTIVASI, DAN KEPUASAN KERJA DAN PENGARUHNYA TERHADAP KOMPETENSI DOSEN DI STKIP BABUNNAJAH PANDEGLANG - Ade Sofyan (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2023)
This study aims to find and analyze the impact of leadership, work environment, motivation, and job satisfaction for improving lecturers' competence at STKIP Babunnajah Pandeglang, which still has a relatively low level of skills. The study is quantitative with a total sample of 65 respondents. In this study, lecturer competency is the dependent variable, and independent variables include leadership, organizational environment, drive, and job satisfaction. To measure the variables, lecturers' perceptions were used to fill in a Likert scale. Data were analyzed by linear regression with two lines using SPSS 22. As a result of the calculation, the feasibility test and classical assumptions were performed on the model; the multiple linear regression equation was found: Y=-0.036+0.257 X1 + 0.019X2 + 0.106 X3 + 0.290 X4. The results prove that lecturer competence is positively and significantly influenced by 76.4 percent of all independent variables; motivation contributes positively but not significantly to lecturer ability; organizational environment, job satisfaction, and leadership also have a positive impact on lecturer competence. 23.6% are additional factors not addressed in this study